Reassessments of thermo-physical properties of Si-Ti melt at different temperatures - Yadav, S K; Mehta, U; Gohivar, R K; Dhungana, A; Koirala, R P; Adhikari, D (BIBECHANA, 2020)
The compositional dependence of thermo-physical properties of Si-Ti liquid alloy has been reassessed using different modeling equations at temperatures 2000 K, 2400 K and 2473 K. The thermodynamic and structural properties of the system have been computed in the frame work of quasi-lattice test. The extent of surface segregation and surface tension of the liquid mixture have been computed using Butler’s equations at afore mentioned temperatures. The results so obtained have been compared with the available literature database. Theoretical investigations shows that the compound forming tendency of the system gradually decreases at elevated temperatures and hence it shows ideal behaviours, as expected. BIBECHANA 17 (2020) 146-153